First Case of Candida auris Colonization in a Preterm, Extremely Low-Birth-Weight Newborn after Vaginal Delivery - Alessio Mesini; Carolina Saffioti; Marcello Mariani; Angelo Florio; Chiara Medici; Andrea Moscatelli; Elio Castagnola (Journal of Fungi, 2021)
Candida auris is a multidrug-resistant, difficult-to-eradicate pathogen that can colonize patients and health-care environments and cause severe infections and nosocomial outbreaks, especially in intensive care units. We observed an extremely low-birth-weight (800 g), preterm neonate born from vaginal delivery from a C. auris colonized mother, who was colonized by C. auris within a few hours after birth. We could not discriminate whether the colonization route was the birth canal or the intensive care unit environment. The infant died on her third day of life because of complications related to prematurity, without signs or symptoms of infections. In contexts with high rates of C.auris colonization, antifungal prophylaxis in low-birth-weight, preterm neonates with micafungin should be considered over fluconazole due to the C. auris resistance profile, at least until its presence is excluded.